Closing ceremony of ICAN Week & Forum on Islamic Social Finance - UiTM, Faculty of Business and Management (UiTM, 2023)
On 30th November 2023, the Faculty of Business and Management at UiTM Puncak Alam officially held the closing ceremony of the ICAN week after a five-day program held from November 27th until December 1st, 2023. The ceremony took place at DK500 located in UiTM Puncak Alam, Selangor. This event was meticulously organized by Academia Teams and the Islamic Banking Student Association (ISBA) in conjunction with ICAN Week. ICAN Week served as a platform that amalgamated various activities at the faculty level, involving industry professionals, the community, and alumni. The objective was to expose and share the insights of industry experts with the students of the Faculty of Business and Management for the purpose of enhancing exposure and the exchange of expertise and experiences. Professor Dr. Firdaus Abdullah, Dean of the Faculty of Business and Management, expressed his gratitude to all who supported the ICAN Week program. He stated that this program had been an important platform for knowledge exchange and to enhance the relationship with the industry. Deputy Rector iCARE UiTM Assoc. Professor Surveyor Dr. Rosmadi Ghazali, Deputy Dean of ICAN FBM Dr. Noor Farradila Abdul Aziz, lecturers, students, and guests from industries attended the event. Meanwhile, the forum was led by Associate Professor Dr. Ismah Osman and two panels from industry. The first panel is Dato' Azrulnizam Abdul Aziz, Chairman of PR1MA Corporation Malaysia and Independent Non-Executive Director of MBSB. The second panel is Dr. Abideen Adiyemi Adewale, who is the Acting Assistant Secretary-General for Standard Implementation of the Islamic Financial Service Board (IFSB).